Hadith #3040 - Sahih al-Bukhari - Ibrahim at-Tamimi's father (Sahih al-Bukhari)
`Ali delivered a sermon saying, “We have no book to read except the Book of Allah and what is written in this paper which contains verdicts regarding (retaliation for) wounds, the ages of the camels (given as Zakat or as blood money) and the fact that Medina is a sanctuary in between Air mountain to so-and-so (mountain). So, whoever innovates in it an heresy or commits a sin or gives shelter in it, to such an innovator will incur the Curse of Allah, the angels and all the people, and none of h
Grade: Sahih

Hadith #7023 - Sahih al-Bukhari - Ibrahim at-Tamimi's father (Sahih al-Bukhari)
`Ali addressed us while he was standing on a brick pulpit and carrying a sword from which was hanging a scroll He said “By Allah, we have no book to read except Allah’s Book and whatever is on this scroll,” And then he unrolled it, and behold, in it was written what sort of camels were to be given as blood money, and there was also written in it: ‘Medina is a sanctuary form ‘Air (mountain) to such and such place so whoever innovates in it an heresy or commits a sin therein, he will inc
Grade: Sahih